A Descriptive Analysis of Project Based Learning Result in ESP Class - Zulfa, Puspa Fortuna (Journal of English for Academic and Specific Purposes (JEASP), 2025)
Project Based learning is a learning model using projects or assignments as a core for learning process. In Project Based Learning, students learn by finishing complex and meaning projects, which are commonly related to real world and require problem solving.  This study aims to describe the result of Project Based Learning in ESP Class. Utilizing qualitative research and descriptive analysis, this research employed Information System and Information Technology major students of first-year to be the objects. The data were obtained from students’ projects in the form of videos that they uploaded on their YouTube channel. Besides, the researcher interviews some students to get additional data and observes students’ activities when finishing the projects. The data analyzed were students’ involvement in solving problems and evaluating creativity and innovation in projects (idea uniqueness, thinking flexibility, explorative skill, new technology innovation and application, resulted effect of solution and collaboration and adaptation). The results showed that project-based learning not only provides students with assignments, but also empowers them with problem-solving and critical thinking strategies. Besides, students were trained to be more responsible and confident with what they have to do suitable with their roles in team respectively. This study contributes to the existing literature by providing empirical evidence of project-based learning results in ESP class. The implications for learning process in ESP class and future research directions are discussed.